2021
DOI: 10.1038/s41380-021-01209-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered cortical thickness development in 22q11.2 deletion syndrome and association with psychotic symptoms

Abstract: Schizophrenia has been extensively associated with reduced cortical thickness (CT), and its neurodevelopmental origin is increasingly acknowledged. However, the exact timing and extent of alterations occurring in preclinical phases remain unclear. With a high prevalence of psychosis, 22q11.2 deletion syndrome (22q11DS) is a neurogenetic disorder that represents a unique opportunity to examine brain maturation in high-risk individuals. In this study, we quantified trajectories of CT maturation in 22q11DS and ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…Anxiety and ADHD symptoms in late childhood (~age 10) are associated with subsequent psychotic symptoms in 22q11.2DS ( Chawner et al, 2019 ; Niarchou et al, 2019 ), although ASD symptoms are not. Brain imaging studies have demonstrated that individuals with 22q11.2DS who developed psychotic symptoms had a trajectory of thicker frontal cortex in childhood and early adolescence, which then more rapidly thinned during adolescence, than individuals with 22q11.2DS who did not develop psychotic symptoms ( Bagautdinova et al, 2021 ; Ramanathan et al, 2017 ). Therefore, increased spindle and SW amplitude in 22q11.2DS in childhood/adolescence could reflect aberrant cortical development processes which clinically associate with ADHD and/or anxiety symptoms in this age group, but then progress to thinner frontal cortex, increased risk of psychotic disorders and potentially decreased spindle/SW density in adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and ADHD symptoms in late childhood (~age 10) are associated with subsequent psychotic symptoms in 22q11.2DS ( Chawner et al, 2019 ; Niarchou et al, 2019 ), although ASD symptoms are not. Brain imaging studies have demonstrated that individuals with 22q11.2DS who developed psychotic symptoms had a trajectory of thicker frontal cortex in childhood and early adolescence, which then more rapidly thinned during adolescence, than individuals with 22q11.2DS who did not develop psychotic symptoms ( Bagautdinova et al, 2021 ; Ramanathan et al, 2017 ). Therefore, increased spindle and SW amplitude in 22q11.2DS in childhood/adolescence could reflect aberrant cortical development processes which clinically associate with ADHD and/or anxiety symptoms in this age group, but then progress to thinner frontal cortex, increased risk of psychotic disorders and potentially decreased spindle/SW density in adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that psychopathology changes with age in 22q11.2DS, including that ADHD symptoms decline with age ( Chawner et al, 2019 ). Therefore, a longitudinal cohort study of sleep EEG biomarkers in 22q11.2DS from childhood and adolescence into adulthood is an important extension of the present study, to elucidate developmental trajectories, as has been achieved with brain imaging ( Bagautdinova et al, 2021 ; Ramanathan et al, 2017 ). Further, a retrospective cohort study of EEGs for those with 22q11.DS who go on to develop schizophrenia-spectrum disorders could dissociate which EEG features relate to the development of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been demonstrated that psychopathology changes with age in 22q11.2DS, including that ADHD symptoms decline with age (Chawner et al, 2019). Therefore, a longitudinal cohort study of sleep EEG biomarkers in 22q11.2DS from childhood and adolescence into adulthood is an important extension of the present study, to elucidate developmental trajectories, as has been achieved with brain imaging(Bagautdinova et al, 2021;Ramanathan et al, 2017). Further, a retrospective cohort study of EEGs for those with 22q11.DS who go on to develop schizophrenia-spectrum disorders could dissociate which EEG features relate to the development of psychosis.…”
mentioning
confidence: 85%
“…The participants included in this study were the control subjects form a larger study from the 22q11DS Swiss Cohort (26)(27)(28). For this study subjects had to be aged between 17 and 30 years, and should not have had any past or present neurological or psychiatric disease, use of psychotropic medications, psychopathology, learning difficulties, or premature birth.…”
Section: Recruitment and Assessment Of Participantsmentioning
confidence: 99%
“…Traditional approaches to EEG analysis involve the decomposition of the EEG signal into functionally distinct frequency bands, each of which has different temporal and topographical characteristics. In adults, typical frequency bands and their approximate spectral boundaries are delta (1-3 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11)(12), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), and gamma (30-100 Hz) (1,2).…”
Section: Introductionmentioning
confidence: 99%